Sacred groves as potential ecotourism sites at Tolon and Diare in Northern Region, Ghana - Benjamin Makimilua Tiimub; Richard Amankwah Kuffour; Richard Wonnsibe Tiimob; Cletus Ankrah Kuuyeni; Ernestina Laatman Tiimob; Elisha Nyannube Tiimob (Journal of Sustainable Tourism and Entrepreneurship, 2020)
Purpose: Relic plant communities commonly referred as “sacred groves” in Ghana and comparatively anywhere are ecologically, genetically important resources indigenously protected as “abodes of gods or ancestral habitats” through traditional or religious beliefs and taboos. This study mainly evaluated the potentials of sacred groves for development as tourist sites at Tolon and Diare in the Northern Region of Ghana. Research methodology: Data was collected using semi structured interview questionnaire aided by vegetation survey, observational field walk through the Jaagbo and Tindangung Sacred Groves to screen natural features of the destinations and determine its potential for ecotourism. Findings: Potential areas for visitor amateurism such as the wonderful baobab tree, crocodile pond, misty stone bird sanctuary, were identified in both groves. About 220 different species of plants were identified in the entire groves. The study further discovered that with effective management measures in place, the ecotourism potentials of these sacred groves will optimize if developed to attract visitors and generate income for sustainable socio-economic development of the adjoining communities in northern Ghana. Limitations: Although the target population was above 200 people, relatively small sample size (? 36%), could be chosen since the opinion leaders considered the groves as sacred and were less prepared to divulge information about them. Islam and Christianity rather counteracted certain beliefs of the traditional people who adopted local measures to enhance sustainability of these sites for ecotourism functions. Contribution: The study advocates the adoption of bylaws to promote sustainable management of the sacred groves for sustainable benefits. Keywords: Jaagbo, Tindangung, Sacred grove, Crocodile pond, Bird sanctuary, Traditional bylaws, Land use plan